Peran Tes Bakat dalam Mengoptimalkan Potensi dan Akademik Siswa - Elya Anggun Wilujeng; Fikhi Dwi Cahyono; Shagusty Widya Satata (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Aptitude test is an assessment tool used to identify an individual's innate abilities in various aspects. In the education sector, aptitude tests have a significant function in maximizing students' abilities and learning progress. This article aims to examine the function of potential tests in education in Indonesia, with an emphasis on their impact on students' academic progress. Through a literature study method, this article evaluates various studies and literature related to aptitude tests and their impact on student achievement. The results of this study indicate that potential tests can support mapping of students' abilities, adjusting teaching methods, and increasing enthusiasm for learning, which ultimately contribute to students' academic progress.